Developer’s willingness to construct green dwellings in China: factors and stimulating policies - He, Chenchen; Wang, Xiaoming; Zhao, Guochao (Journal of Civil Engineering and Management, 2018)
Green dwelling (GD) is a way to mitigate impacts of the building stock on environment and provide a better living condition for residences. However, the number of GDs is relatively small. Especially in China, GDs only account for less than 0.4% of the total buildings. It is directly due to the shortage of supply, which is influenced by the lack of willingness to develop. To stimulate the GD diffusion, the study applies structural equation model to analyse the factors in developers’ willingness to construct GDs, considering the inter-relationships and relative inﬂuences among factors. Further, it calculates the influence of each policy and policy subseries on developers’ willingness. It is showed that developers’ willingness is mostly influenced by their developing ability, followed by market development. Then comes government policy and corporate responsibility. In terms of stimulating policies on developers’ willingness, floor-to-area density award is of the biggest impact, followed by the green building requirement and interest rare. As to the policy subseries, mandatory requirements has larger effects on developers then voluntary incentives. Besides, in China, developers are more sensitive to financial incentives than non-financial ones. Accordingly, suggestions for policy making are proposed to stimulate developers to construct GDs.